Environmental Management of Liboganik Organic Fertilizer Plant from Solid Palm Oil Waste in Pauh Village, Bonai Darussalam District, Rokan Hulu Regency, Indonesia - Hartanto, Farhan Sidiq; Putra, Ridwan Manda; Nurhidayah, Tengku; Amin, Bintal; Budijono, Budijono; Yusmarini (UIR PRESS, 2025)
This study was designed to analyze and examined the environmental management strategy of Liboganik solid organic fertilizer factory derived from solid palm oil waste in Pauh Village, Bonai Darussalam District, Rokan Hulu Regency, Riau. The study used a qualitative approach method using questionnaire and interview instruments as well as laboratory tests conducted with samples of company leader, factory employees, communities around the fertilizer factory and palm oil farmers totaling 63 and selected randomly. The results of the study showed that the water quality of the Liboganik organic fertilizer factory waste was polluted, as seen from the data from the physical parameter laboratory tests above, it can be seen that the suspended solids (TSS) content and COD content exceed the standard COD waste standards for organic fertilizer factories according to the standard of the Minister of Environment Regulation No. 5 of 2014 concerning Wastewater Quality Standards. Environmental management can be carried out through the spatial planning of fertilizer factory buildings as well as through the construction of adequate infrastructure and paying attention to its impact on the environment and factory workers in order to encourage the realization of an environmentally friendly fertilizer factory. It is concluded that environmental management of organic fertilizer factories can be done by making a ditch pond to accommodate seepage of residual palm oil factory waste and limiting it so that pollution does not occur to the community environment. In addition, in an effort to reduce high COD and BOD content, wastewater management can be carried out using Phytoremediation techniques and also technology using Vertical Water Circulation (SAV). The results of IFAS and EFAS as well as SWOT analysis concluded that the environmental management strategy of the Liboganik organic fertilizer factory is in the SO quadrant and is included in Aggressive Strategy.